KEPERCAYAAN MENDORONG NIAT INDIVIDU UNTUK MELAKUKAN SOCIAL COMMERCE - Akbar, Muhammad; Nugroho, Agung Dwi; Andini, Ena; Hidayatullah, Amir (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jawa Tengah, 2020)
The research objective is to analyze the role of trust to encourage individuals to do social commerce. The population in this study is internet users. The sample in this study were social media users. The sampling technique in this study uses purposive sampling, with the criteria of social media users who have made at least two purchases through social media they have. Data in the study were collected by distributing questionnaires with the help of Google Form. Respondents in the study numbered 152 respondents. Data analysis techniques in this study used Partial Least Square (PLS) with the help of WarpPLS. The study found that the intention to make purchases through social media was influenced by trust, perceived ease of use, and perceived usefulness. In addition, this study also obtained results that the perception of ease of use affects the perception of usefulness